Non-supersymmetric attractors in BI black holes - Chandrasekhar, B. [UNESP]; Yavartanoo, H.; Yun, S. (Elsevier B.V., 2008)
We study attractor mechanism in extremal black holes of Einstein-Born-Infeld theories in four dimensions. We look for solutions which are regular near the horizon and show that they exist and enjoy the attractor behavior. The attractor point is determined by extremization of the effective potential at the horizon. This analysis includes the backreaction and supports the validity of non-supersymmetric attractors in the presence of higher derivative interactions in the gauge field part. (C) 2008 Elsevier B.V. All rights reserved.